A Review on Future Safety Mechanisms in Automated Vehicle Management Systems - Omkar Hundekari; Avishkar Pachpute; Darshan Bachhav (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
This Concept is totally based on maximum safety provisions in future vehicles. The Main idea behind this concept is to provide such features with a lot of daily incidents which can be Fatal or Non-Fatal that can be easily avoided with the help of AI and the overall system. With an overall analysis most of the accidents take place with minor human errors and turn out to be fatal. The Basic idea behind this concept is to connect all cars/vehicles together via GPS, AI within a certain radius and the car can itself detect any incoming vehicles towards it from any direction and the AI can take the necessary controls of the car if the driver is not able to detect the car.